What Works in Conservation 2021 - Sutherland, William J.; Dicks, Lynn V.; Petrovan, Silviu O.; Smith, Rebecca K. (What Works in Conservation, 2021)
"Does the creation of artificial reefs benefit subtidal benthic invertebrates? Is the use of organic farming instead of conventional farming beneficial to bat conservation? Does installing wildlife warning reflectors along roads benefit mammal conservation? Does the installation of exclusion and/or escape devices on fishing nets benefit marine and freshwater mammal conservation? What Works in Conservation has been created to provide practitioners with answers to these and many other questions about practical conservation. This book provides an assessment of the effectiveness of 2526 conservation interventions based on summarized scientific evidence. The 2021 edition containssubstantial new material on bat conservation, terrestrial mammal conservation and marine and freshwater mammals, thus completing the evidence for all mammal species categories. Other chapters cover practical global conservation of primates, amphibians, bats, birds, forests, peatlands, subtidal benthic invertebrates, shrublands and heathlands, as well as the conservation of European farmland biodiversity and some aspects of enhancing natural pest control, enhancing soil fertility, management of captive animals and control of freshwater invasive species. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually, and provides full references. This is the sixth author-approved edition of What Works in Conservation, which is revised on an annual basis. "